2003
DOI: 10.1021/jp027396g
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Adiabatic and Nonadiabatic Pathways in the Photodissociation of Vibrationally Excited Ammonia

Abstract: Vibrationally mediated photodissociation combined with Doppler spectroscopy and time-of-flight detection of H-atoms provides information on the photofragmentation dynamics from selected rovibrational states of à 1 A 2 ′′-state ammonia. The competition between adiabatic dissociation forming excited-state NH 2 ( 2 A 1 ) + H and nonadiabatic dissociation leading to ground-state NH 2 ( 2 B 1 ) + H products changes drastically for dissociation from different parent levels prepared by double-resonance excitation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 26 publications
3
49
0
Order By: Relevance
“…The photodissociation patterns of the excited NH 3 (Ã 1 A 2 ) strongly depend on the vibrational mode being excited [43]. Figure 7 shows one-dimensional cuts through the potential surfaces for slightly nonplanar geometries with a trisector angle of 77.4 • in both C s and C 1 symmetries; U 22 is dashed.…”
Section: Discussionmentioning
confidence: 99%
“…The photodissociation patterns of the excited NH 3 (Ã 1 A 2 ) strongly depend on the vibrational mode being excited [43]. Figure 7 shows one-dimensional cuts through the potential surfaces for slightly nonplanar geometries with a trisector angle of 77.4 • in both C s and C 1 symmetries; U 22 is dashed.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Strong mode and bond selectivity has been found. 24,[30][31][32][33][34][35][36][37] One of the most intriguing findings in the vibrationally mediated ammonia photodissociation is the strong mode selectivity of the NH 2 (Ã 2 A 1 )/NH 2 (X 2 B 1 ) branching ratio. 34,37 Unlike the commonly observed dominance of the ground state NH 2 (X 2 B 1 ) channel, excitation in the antisymmetric stretching mode of NH 3 prior to photolysis resulted in mostly adiabatic dissociation to NH 2 (Ã 2 A 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of experiments and calculations on molecules with conical intersections in which the influence of one or more conical intersections on internal conversion or decomposition pathways is apparent [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. We have demonstrated that vibrational excitation can alter the probability of a molecule passing through a conical intersection by changing the trajectory that carries the system into the intersection [20,21]. In general, preparing molecules in a selected vibrational state prior to electronic excitation can alter dissociation dynamics and pathways by allowing the photoexcitation step to reach normally inaccessible regions of the excited-state potential.…”
Section: Introductionmentioning
confidence: 99%
“…The photolysis of ammonia is a prototypical example of dissociation through a conical intersection between two electronic states, and its study has shaped many ideas about the dissociation involving a conical intersection [20][21][22][23][24][25][26][27][28][29]. The adiabatic decomposition of electronically excited NH 3 (Ã 1 A 00 2 ) produces a hydrogen atom and an electronically excited fragment NH Ã 2 (H þ NH 2 ( 2 A 1 )), and the nonadiabatic decomposition *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation